Combined effects of machining-induced residual stress and external load on SCC initiation and early propagation of 316 stainless steel in high temperature high pressure water. (September 2021) - Zhang, Wenqian; Wang, Xuelin; Wang, Siyang; Wu, Huanchun; Yang, Chongwen; Hu, Yujin; Fang, Kewei; Jiang, Hui
Highlights: SCC initiation was related to the resultant stress of residual stress and external load. The biaxial stress state with high SCC susceptibility was obtained. Individual effects of residual stress and external load on SCC were emphasized. Abstract: Combined effects of machining-induced residual stress and external load on stress corrosion cracking (SCC) initiation and early propagation of 316 stainless steel were explored in high temperature high pressure water environment. Three different external loads were applied to machined specimens with varied residual stresses. The results revealed that the residual stress promoted SCC initiation while the external load further contributed to continuous crack propagation. Additionally, it was found the SCC initiation and early propagation were highly related to biaxial stress state. The biaxial stress state with high SCC susceptibility at 300 °C water environment was obtained.